2010
DOI: 10.1002/jbm.b.31598
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) films for topical delivery of S‐nitrosoglutathione: Effect of freezing–thawing on the diffusion properties

Abstract: Poly(vinyl alcohol) (PVA) is a biocompatible polymer already used in several pharmaceutical products. The purpose of this work was to investigate the influence of freezing-thawing cycles (F/T) on the in vitro diffusion and skin vasodilator properties of S-nitrosoglutathione (GSNO)-releasing PVA films. Films subjected to 1-, 3-, and 5-F/T showed an increase in crystallinity, which is associated with an increase in the radius of gyration of macropores from 155 to 180 nm. Diffusion coefficients (D) of GSNO decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…GSNO has been administered through intravenous infusion [127], as an aerosolized inhalant [128], and more recently, as a topical gel [129] and poly vinyl alcohol film [130]. The best-characterized effects of GSNO in humans are on its direct and selective action in platelets.…”
Section: Use Of Gsno In Human Clinical Trialsmentioning
confidence: 99%
“…GSNO has been administered through intravenous infusion [127], as an aerosolized inhalant [128], and more recently, as a topical gel [129] and poly vinyl alcohol film [130]. The best-characterized effects of GSNO in humans are on its direct and selective action in platelets.…”
Section: Use Of Gsno In Human Clinical Trialsmentioning
confidence: 99%
“…In a recent study done by Simoes and de Oliveira, PVA hydrogels with GSNO addition were prepared using the freezing-thawing (F/T) technique. [73] It was found that the pore size of PVA hydrogels decreased with increasing F/T cycles, whereas the crystallinity rose. NO diffusion coefficient depended not only on the pore size of the hydrogels, but also on the interconnectivity of the pores.…”
Section: Hydrogelsmentioning
confidence: 99%
“…PVA films (~50 mg) absorbed 450 μmol g −1 or 840 μmol g −1 of GSNO with one or five freeze/thawed (F/T) cycles, respectively. [166] Upon one F/T cycle, the crystallinity and physical cross-linking increased and was not different between one and five F/T cycles. However, the GSNO absorption and diffusion coefficient varied with F/T cycle number (one F/T: 2.0 · 10 −7 cm 2 s −1 , five F/T: 5.0 · 10 −7 cm 2 s −1 ), possibly because of greater interconnected pores with more cycles.…”
Section: Progress In the In Vivo Application Of No-releasing And Nmentioning
confidence: 99%